The Gambia : Economic Adjustment in a Small Open Economy - Verreydt, Eric (Occasional Papers; Occasional Paper, 1992)
The Gambia, one of the least developed countries in Africa, has been pursuing corrective economic policies since 1985, aimed at restroing financial stability and laying the basis for strong and sustainable economic growth. Supported by IMF policy advice and financing. The Gambia's economic performance has improved considerably since 1985. This study discusses Gambian adjustment policies and their benefits.